Emerging real estate markets: - Lindahl, David (John Wiley & Sons, 2008)
While many real estate markets have cooled off, there are major hot spots throughout the country that are booming due to population growth and urban expansion. These emerging markets are where the next wave of big-time real estate profits will be found. In Emerging Real Estate Markets, David Lindahl shows you how to find these markets, get started investing with little of your own cash, and maximize your profits.